Monetary redress for abuse in state care / Stephen Winter. - Winter, Stephen (Cambridge University Press, 2023)
Investigating a fast-developing field of public policy, Stephen Winter examines how states redress injuries suffered by young people in state care. Considering ten illustrative exemplar programmes from Australia, Canada, Ireland, and Aotearoa New Zealand, Winter explores how redress programmes attempt to resolve the anguish, injustice, and legacies of trauma that survivors experience. Drawing from interviews with key stakeholders and a rich trove of documentary research, this book analyses how policymakers should navigate the trade-offs that survivors face between having their injuries acknowledged and the difficult, often retraumatising, experience of attaining redress. A timely critical engagement with this contentious policy domain, Winter presents empirically driven recommendations and a compelling argument for participatory, flexible, and survivor-focussed programmes.